Xây dựng hệ thiết bị tự động xác định thời gian đáp ứng của một số sensơ oxi kiểu Clark - Hà, Vũ Thị Thu (Vietnam Journal of Chemistry, 2012)
An equipment system consisting of a computer and actuators have been installed in Institute of Chemistry for measurement of response time of home-made Clark oxygen sensors. Working electrodes as cathodic were made from gold and platinum wires with various diameters. Two solution corresponding to saturated oxygen concentration and none oxygen (DO equal to zero) solution were used for response time measurements. Switching between two oxygen level and reading output signals were controlled by the mentioned system with concerning software, which also carried out all treatment of obtained data and calculation of response time. In case of studied Clark oxygen sensors using gold single microelectrode, array gold microelectrode, platinum and conventional gold, their response time were determined as 6s, 10s, 18s and 23s respectively. The results show advantages of the designed system, which can be considered as a helpful tool for investigation of various  kind of sensor’s characteristics